Phosphogypsum modified acid-activated geopolymer and preparation method thereof
By using phosphogypsum modified acid-exciting polymers in phosphogypsum base polymers, the problem of degradation of performance of phosphogypsum base polymers is solved, and a material with denser structure and better mechanical properties is achieved , suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202411481332.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
AI Technical Summary
Phosphogypsum base polymers have deteriorated performance in certain corrosive environments or high temperature conditions, and have disadvantages such as high brittleness and poor toughness, making it difficult to meet the requirements of use in harsh environments.
Using phosphogypsum modified acid-excited polymers, a material with a denser structure and better mechanical properties is formed through specific raw materials composition and preparation methods. The material includes phosphogypsum, fly ash, metakaolin, acid exciter and water. It forms a three-dimensional network structure through acid excitation reaction, maintains an electrically neutral state, avoids additional metal cation balance, and is suitable for use as an insulator material.
It realizes the stable performance of acid-excited earth polymer in extreme environments, has better mechanical properties and durability, avoids the problems of poor brittleness and toughness of alkali-excited earth polymers, and is suitable for building materials, environmentally friendly materials and high performance. Composite materials field.
Smart Images

Figure CN119430708A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of inorganic geopolymers and preparation methods thereof, and in particular to a phosphogypsum-modified acid-activated geopolymer and a preparation method thereof. Background Art
[0002] Phosphogypsum is a byproduct of the industrial wet process phosphoric acid production and is considered an industrial waste. Generally, 4.5 to 5.5 tons of phosphogypsum will be produced for every ton of phosphoric acid produced by the wet process. The main component of phosphogypsum is calcium sulfate dihydrate (CaSO 4 ·2H 2 O), and also contains many impurities, such as phosphorus impurities, fluorine impurities, residual acid and sulfate, and even trace heavy metal elements and radioactive elements. Although phosphogypsum has a wide range of applications and is currently mainly used in the fields of building materials and chemical industry, the influence of impurities has seriously limited the promotion and application of phosphogypsum, resulting in an increase in its storage volume year by year. For example, the presence of soluble phosphorus in phosphorus impurities will affect the hydration and hardening time of phosphogypsum; in addition, fluoride will reduce the compressive strength and flexural strength of phosphogypsum. Large amounts of stockpiled phosphogypsum will not only waste land resources, but also have a huge impact on the environment around the stacking site. Its harmful impurities will also penetrate into groundwater or flow into rivers, lakes and reservoirs, thereby damaging human health. Therefore, improving the harmless resource utilization rate of phosphogypsum is an issue that needs to be urgently addressed.
[0003] Phosphogypsum alkali-activated geopolymer refers to an inorganic polymer with a three-dimensional network structure formed by using phosphogypsum as a raw material and reacting with active aluminosilicate minerals (such as metakaolin, slag, etc.) under the action of an activator (such as sodium silicate, sodium hydroxide, etc.). By preparing the geopolymer through an alkali-activated reaction, harmful impurities (such as fluoride, phosphorus pentoxide, etc.) in the phosphogypsum can be effectively fixed in the geopolymer structure, thereby reducing its pollution to the environment. At the same time, as an industrial by-product, phosphogypsum can be converted into a material with use value through an alkali-activated reaction, thereby realizing the recycling of resources. For example, the invention patent application with publication number CN115159874A discloses a phosphogypsum-based polymer, which includes 50 parts of phosphogypsum, 450 parts of slag, 500 parts of fly ash, 329-397 parts of water, 375-384 parts of an alkali activator, and 10 parts of a retarder. The invention mixes phosphogypsum, fly ash and slag into a cementitious material, which can replace cement to reduce the use of cement. It interacts with retarders and alkali activators to shift the charge distribution in Si-O-Si and Al-O-Al covalent bonds, and break the Al-O and Si-O bonds, forming a material with excellent stability and durability.
[0004] Although the above-mentioned phosphogypsum-based polymer has a certain durability, in certain corrosive environments or high temperature conditions, contact with strong oxidizing or reducing substances will cause the molecular chain of the material to break or lose its original characteristics, resulting in a decline in material performance or failure. In addition, the above-mentioned phosphogypsum-based polymer has the disadvantages of high brittleness and poor toughness. It is easy to crack and age when exposed to the external environment for a long time due to erosion. Therefore, the durability and stability of the above-mentioned phosphogypsum-based polymer still cannot meet the use requirements in certain harsh environments. Summary of the invention
[0005] The purpose of the present application is to provide a phosphogypsum-modified acid-activated geopolymer and a preparation method thereof, so as to solve the problem that the durability and stability of the phosphogypsum-based polymer in the related art still cannot meet the use requirements in certain harsh environments.
[0006] In the first aspect, the present application provides a phosphogypsum-modified acid-activated geopolymer using the following technical solution:
[0007] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 36-144 parts of fly ash, 576-684 parts of metakaolin, 388.8-611.58 parts of acid activator and 200.11-261 parts of water.
[0008] Optionally, the acid activator is phosphoric acid.
[0009] Optionally, the phosphogypsum-modified acid-activated geopolymer includes the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 388.8 parts of phosphoric acid and 261 parts of water.
[0010] In the second aspect, the present application provides a method for preparing a phosphogypsum-modified acid-activated geopolymer using the following technical solution:
[0011] A method for preparing a phosphogypsum modified acid-activated geopolymer is provided, wherein the method comprises preparing the phosphogypsum modified acid-activated geopolymer according to the raw material components of the phosphogypsum modified acid-activated geopolymer.
[0012] Optionally, the method for preparing the phosphogypsum modified acid-activated geopolymer comprises the following steps:
[0013] S1. Mix phosphoric acid and water to make a phosphoric acid solution, and let it stand to room temperature;
[0014] S2. The phosphogypsum, fly ash and kaolin are stirred and mixed evenly, and then the prepared phosphoric acid solution is poured and stirred and mixed evenly to form a slurry;
[0015] S3. Pour the slurry into the mold, vibrate to eliminate bubbles in the slurry, and smooth the surface;
[0016] S4. Curing and demolding the slurry to prepare phosphogypsum modified acid-activated geopolymer.
[0017] Optionally, in step S4, the steps of curing and demolding the slurry are as follows: wrapping the outside of the mold with a plastic film, then putting it into a plastic bag, spraying water in the plastic bag, and sealing the plastic bag, curing it in an environment with a temperature of 55°C for 1 day, and then continuing to cure it at room temperature for 7 days after demolding.
[0018] Optionally, in step S4, the steps of curing and demolding the slurry are as follows: placing the mold in a steam curing chamber for steam curing to solidify the slurry in the mold, then demolding the module in the mold, and coating the outside of the module with a hydrogel layer, then coating the outer wall of the hydrogel layer with a water-retaining film, and then curing the module at room temperature for 7-10 days before removing the hydrogel layer and the water-retaining film.
[0019] Optionally, the hydrogel layer comprises the following raw material components in parts by weight: 320-360 parts of starch, 200-240 parts of gelatin, 40-50 parts of sodium silicate, 60-75 parts of hyaluronic acid, 20-25 parts of sodium polyacrylate, 16-23 parts of acrylamide, 8-14 parts of ammonium persulfate, 7-10 parts of calcium carbonate, 5-8 parts of polyethylene glycol, 5-10 parts of sodium lactate, 12-15 parts of stearyl alcohol, 2-6 parts of calcium chloride and 210-250 parts of water;
[0020] The step of wrapping the hydrogel layer on the outside of the module is as follows: placing the module after steam curing and demoulding in a box, so that the module is in contact with the inner bottom wall of the box, and the side wall of the module is spaced from the inner side wall of the box, mixing and stirring the raw materials of the hydrogel layer to evenly form a slurry, then injecting a portion of the slurry into the box and submerging the module, and leaving the box at a temperature of 42-50° C. for 1.5-2 hours to allow the slurry to condense into a solid hydrogel layer and coat the outside of the side wall and top wall of the module, then taking the module and the hydrogel layer out of the box, turning them 180 degrees, and then placing them back in the box, injecting the remaining slurry into the box and submerging the module, and then leaving the box at a temperature of 42-50° C. for 1.2-1.8 hours to allow the slurry to condense into a solid hydrogel layer and completely coat the outside of the module, and then taking the module and the hydrogel layer coating the outside of the module out of the box.
[0021] Optionally, the steam curing steps are as follows: wrap a plastic film on the surface of the mold, place the mold in a steam curing room at a temperature of 20-30°C and let it stand for 4-8 hours, then introduce steam into the steam curing room to raise the temperature in the steam curing room to 60-80°C, and control the temperature rise rate to 5-10°C / h, then maintain a constant temperature for 12-16 hours, then reduce the temperature in the steam curing room to 30-40°C, and control the cooling rate to 6-9°C / h, and then demold to complete the steam curing.
[0022] Optionally, the water-retaining film comprises the following raw material components in parts by weight: 5-10 parts of dimer acid polyester polyol, 5-8 parts of hexafluorobutyl methacrylate, 10-15 parts of ethylene glycol, 2-4 parts of stannous isooctanoate, 30-40 parts of paraffin wax, 6-8 parts of zinc stearate, 12-15 parts of oxidized polyethylene wax, 8-10 parts of ethylene bisstearamide and 50-60 parts of water;
[0023] The steps of coating the water-retaining film on the outer wall of the hydrogel layer are as follows: the raw materials of the water-retaining film are mixed and stirred evenly to form a coating, a layer of coating is applied on the outer wall of the hydrogel layer, and another layer is applied after the coating is dried, and this is repeated for 5-10 layers to form a water-retaining film.
[0024] In summary, the present application at least includes the following beneficial technical effects: the acid-activated geopolymer modified by the phosphogypsum by weight ratio of the raw material components and the preparation method of the present application is compared with the alkali-activated geopolymer, and the three-dimensional structure of the acid-activated geopolymer can basically maintain the electrical neutrality state, and does not require additional metal cations for electrical balance, so the acid-activated geopolymer can be used as an insulator material, and at the same time, since there are no large-radius metal ions occupying the space of the three-dimensional network structure, a more compact structure can be formed, that is, better mechanical properties and durability can be exhibited, while the alkali-activated geopolymer usually has the disadvantages of large brittleness and poor toughness. Acid-activated geopolymers usually show better durability due to their compact structure, high temperature stability, low dielectric constant and low dielectric loss, and these characteristics enable acid-activated geopolymers to maintain stable performance even in extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM photograph of a phosphogypsum-modified acid-activated geopolymer sample not mixed with phosphogypsum acid-activated in Example 1 of the present application;
[0026] Figure 2 This is a SEM photograph of the acid-activated test block of the phosphogypsum-modified acid-activated geopolymer in Example 1 of the present application after the phosphogypsum was added. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0030] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 388.8 parts of phosphoric acid and 261 parts of water.
[0031] The phosphogypsum (PG) used in this example is provided by Hubei Xiangyun Chemical Industry Co., Ltd. and is a light gray or dark gray solid. The morphology test by scanning electron microscope (SEM) shows that the phosphogypsum particles are regular prisms and plates. The density is 2.34 g / cm3 as measured by the pycnometer method. 3 The moisture content was 10.3%-11.3% as determined by drying method. The main component was dihydrate gypsum (Gypsum, Ca 2 SO 4 ·2H 2 O) and quartz (Quartz, SiO 2 ), the X-ray fluorescence spectrometry analysis (XRF, PANalyticalAxios, produced in the Netherlands) of phosphogypsum is shown in Table 2. It can be seen that the main content of SO 3 , CaO and SiO 2 When using phosphogypsum, it is dried at a temperature of 55±5℃ and crushed by simple rolling and then passed through a 0.3mm standard sieve.
[0032] The fly ash (FA) used was produced by Wuhan Iron and Steel Co., Ltd., and was of grade I low-calcium fly ash. It was a gray powdery solid. The SEM morphology test showed that the fly ash particles were regular spherical. The 0.045 mm square hole sieve residue of the fly ash was 10.4%. According to GB / T8074-2008 "Determination of specific surface area of cement by Blaine method", the Blaine specific surface area of the fly ash used in the experiment was 425 m 2 / kg. Through XRD test, it is known that the main components of fly ash are mullite, sillimanite and quartz; the XRF test results of fly ash are shown in Appendix 1, and it is known that the main components are Al2 O 3 and SiO 2 And a small amount of CaO.
[0033] The metakaolin (MK) used was provided by Gongyi Chenyi Refractory Abrasive Co., Ltd. The material is made by crushing, grinding and calcining kaolinite and is a reddish brown powder. The XRF test results of metakaolin are shown in Table 2. It can be seen that the main chemical composition of metakaolin is silicon dioxide and aluminum oxide, of which SiO 2 The proportion is 47.097%, Al 2 O 3 The proportion is 44.919%.
[0034] The acid activator used is phosphoric acid with a mass fraction of 85%. Phosphoric acid is a medium-strong acid that can be miscible with water in any proportion. It has a density of 1.874 g / ml and is a colorless viscous liquid. The water used is deionized water.
[0035] Appendix 1 Chemical composition of fly ash (wt.%)
[0036]
[0037] Appendix 2 Chemical composition of metakaolin and phosphogypsum (wt.%)
[0038]
[0039] The embodiments of the present application also disclose a method for preparing phosphogypsum-modified acid-activated geopolymer.
[0040] A method for preparing a phosphogypsum-modified acid-activated geopolymer is prepared according to the raw material components of the phosphogypsum-modified acid-activated geopolymer, and comprises the following steps:
[0041] S1. Use an electronic balance to weigh the required phosphoric acid and water respectively, pour them into a beaker and stir them continuously with a glass rod to mix the phosphoric acid and water evenly to make a phosphoric acid solution, and let it stand to room temperature;
[0042] S2. Weigh the required phosphogypsum, fly ash and kaolin, add the phosphogypsum, fly ash and kaolin to a stirring pot, stir for two minutes to mix them evenly, then pour the prepared phosphoric acid solution, and stir at high speed to mix evenly to form a slurry;
[0043] S3. Pour the slurry into a 40mm×40mm×40mm triple plastic mold, eliminate the bubbles generated during stirring in the slurry by vibration on a vibration table, and use a scraper to flatten the surface;
[0044] S4. Curing and demolding the slurry to prepare a phosphogypsum-modified acid-activated geopolymer;
[0045] In step S4, the steps of curing and demolding the slurry are as follows: a plastic film is coated on the outside of the mold, and then it is placed in a plastic fresh-keeping bag, a small amount of water is sprayed in the plastic fresh-keeping bag with a spray bottle, and the plastic fresh-keeping bag is sealed to prevent water evaporation. Then the mold is placed in an oven or a constant temperature curing box at a temperature of 55°C for 1 day to shape the slurry, and then the molded module is removed from the mold, and it is placed in a plastic fresh-keeping bag, sealed, and continued to be cured at room temperature for 7 days.
[0046] The spherical particles in the fly ash in the phosphogypsum-modified acid-activated geopolymer of this embodiment can disperse the gel produced in the reaction and increase the contact area. When the fly ash adopts the weight proportion of this embodiment, the compressive strength of the test block can be effectively increased. At the same time, the Ca element in the fly ash participates in the reaction to generate a large amount of heat, which makes the water in the system evaporate rapidly. The produced calcium phosphate compound also captures a large amount of free water and converts it into its crystal water, thereby shortening the setting time of the acid-activated geopolymer. However, when the fly ash is excessive, a large amount of spherical particles will remain in the product, resulting in cracks, which will have an adverse effect on the mechanical properties of the acid-activated geopolymer.
[0047] See attached Figure 1 and 2 , by adding the weight fraction of phosphogypsum of the present embodiment, phosphogypsum can construct a multi-dimensional network structure in the acid-activated geopolymer matrix through its unique plate-like structure. This network structure not only enhances the overall skeleton support of the material, but also promotes the uniform distribution of stress inside the material, effectively preventing the damage caused by local stress concentration. At the same time, the plate-like crystals of phosphogypsum can also serve as nucleation sites to promote the crystal phase transformation of the acid-activated geopolymer during the solidification process, and further optimize the microstructure and performance of the material. Phosphogypsum can also provide the acidic environment required for the reaction, and can corrode the solid surface of the metal oxide in the metakaolin, increase the contact area of the reactants, promote the depolymerization-condensation process of the acid-activated geopolymer, and increase the reaction rate. The phosphorus in the phosphogypsum can also adjust the setting time of the test block, shorten the initial setting and final setting time of the test piece, so that the early strength of the acid-activated geopolymer is further enhanced. However, when the phosphogypsum is excessive, too much phosphogypsum will occupy too much space, resulting in a reduction in the effective contact area between the reactants, thereby hindering the full progress of the chemical reaction. This will not only reduce the strength of the product, but also may affect the uniformity and consistency of the material. In addition, excessive phosphogypsum may also cause volume expansion and cracking of the material, reducing the mechanical properties.
[0048] In terms of environmental protection, the rational use of phosphogypsum by the acid-activated geopolymer modified with phosphogypsum in this embodiment not only solves the environmental pollution problem caused by its storage, but also realizes the recycling of resources. By converting it into high-performance building materials, it not only reduces the exploitation of natural resources, but also reduces the carbon emissions of the construction industry, which is in line with the concept of sustainable development.
[0049] The phosphogypsum modified acid-activated geopolymer prepared by the preparation method of this embodiment has the following advantages:
[0050] 1. Greenness of materials
[0051] The raw materials of acid-activated geopolymers are industrial waste / by-products such as fly ash and phosphogypsum, which provides a new path to solve the accumulation of solid waste. The acid-activated geopolymer prepared in this embodiment is mixed with two solid waste materials-phosphogypsum and fly ash. By adopting the raw material components of the weight proportions in this embodiment, the mechanical properties and working performance of the test block can be effectively improved, and at the same time, the phosphogypsum and fly ash are wrapped in the three-dimensional network structure of "-Si-O-P-O-Al-" produced by the acid-activated geopolymer as the basic chemical unit, which has good solid waste accommodation capacity. Since acid-activated geopolymers use acidic activators in the preparation process, they may cause less environmental pollution than alkaline activators. In particular, alkali-aggregate reaction is not easy to occur during acid activation, which is of great significance to the long-term stability and durability of concrete structures.
[0052] 2. Material performance advantages
[0053] The phosphogypsum modified acid-activated geopolymer prepared by the raw material components and preparation method of the weight parts of the present embodiment is compared to alkali-activated geopolymer, the three-dimensional structure of acid-activated geopolymer can basically maintain an electrically neutral state, does not need extra metal cations to carry out electrical balance, so acid-activated geopolymer can be used as an insulator material, simultaneously because there is no metal ion with a large radius to occupy the space of the three-dimensional network structure, a more compact structure can be formed, which can show better mechanical properties and durability, and alkali-activated geopolymer usually has shortcomings such as large brittleness and poor toughness. Acid-activated geopolymer usually shows better durability due to the characteristics of compact structure, high temperature stability, low dielectric constant and low dielectric loss, and these characteristics make acid-activated geopolymer also can keep stable performance under extreme environment. Although alkali-activated geopolymer also has certain durability, under some corrosive environments or high temperature conditions, its performance can be easily affected. Furthermore, due to the addition of phosphogypsum and fly ash, some gaps are filled and the setting time is adjusted. Therefore, the phosphogypsum modified acid-activated geopolymer prepared by the preparation method of this embodiment can show better working performance and mechanical properties.
[0054] 3. Advantages of material application prospects
[0055] Due to its unique performance advantages, the phosphogypsum modified acid-activated geopolymer prepared by the preparation method of this embodiment has broad application prospects in the fields of building materials, environmentally friendly materials, high-performance composite materials, etc. In particular, acid-activated geopolymer materials will play an important role in projects with high requirements for strength and durability.
[0056] Example 2
[0057] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0058] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 36 parts of fly ash, 684 parts of metakaolin, 611.58 parts of phosphoric acid and 200.11 parts of water.
[0059] The present application also discloses a method for preparing a phosphogypsum-modified acid-activated geopolymer. The difference between the method for preparing a phosphogypsum-modified acid-activated geopolymer in this embodiment and that in embodiment 1 is that:
[0060] In step S4, the steps of curing and demolding the slurry are as follows: placing the mold in a steam curing chamber for steam curing to solidify the slurry in the mold, then demolding the module in the mold, and coating the outside of the module with a hydrogel layer, then coating the outer wall of the hydrogel layer with a water-retaining film, and then curing the module at room temperature for 7 days before removing the hydrogel layer and the water-retaining film.
[0061] The steps of steam curing are as follows: wrap a plastic film on the surface of the mold, place the mold in a steam curing room at a temperature of 20°C and let it stand for 4 hours, then introduce steam into the steam curing room to raise the temperature in the steam curing room to 60°C, and control the temperature rise rate to 5°C / h, then maintain constant temperature for 12 hours, then reduce the temperature in the steam curing room to 30°C, and control the cooling rate to 6°C / h, then demold and complete steam curing.
[0062] The hydrogel layer includes the following raw material components in parts by weight: 320 parts of starch, 200 parts of gelatin, 40 parts of sodium silicate, 60 parts of hyaluronic acid, 20 parts of sodium polyacrylate, 16 parts of acrylamide, 8 parts of ammonium persulfate, 7 parts of calcium carbonate, 5 parts of polyethylene glycol, 5 parts of sodium lactate, 12 parts of stearyl alcohol, 2 parts of calcium chloride and 210 parts of water.
[0063] The steps of wrapping the hydrogel layer on the outside of the module are as follows: placing the module after steam curing and demolding in a box, so that the module is in contact with the inner bottom wall of the box, and the side wall of the module is spaced from the inner wall of the box, the raw materials of the hydrogel layer are mixed and stirred evenly to form a slurry, and then a part of the slurry is injected into the box and submerged into the module, and the box is allowed to stand for 1.5 hours in an environment with a temperature of 42°C, so that the slurry condenses into a solid hydrogel layer and is coated on the outside of the side walls and top wall of the module, and then the module and the hydrogel layer are taken out of the box and turned 180 degrees and placed back in the box, and the remaining slurry is injected into the box and submerged into the module, and the box is allowed to stand for 1.2 hours in an environment with a temperature of 42°C, so that the slurry condenses into a solid hydrogel layer and completely coats the outside of the module, and then the module and the hydrogel layer coating the outside of the module are taken out of the box.
[0064] The water-retaining film comprises the following raw material components in parts by weight: 5 parts of dimer acid polyester polyol, 5 parts of hexafluorobutyl methacrylate, 10 parts of ethylene glycol, 2 parts of stannous isooctanoate, 30 parts of paraffin wax, 6 parts of zinc stearate, 12 parts of oxidized polyethylene wax, 8 parts of ethylene bisstearamide and 50 parts of water.
[0065] The steps of coating the water-retaining film on the outer wall of the hydrogel layer are as follows: the raw materials of the water-retaining film are mixed and stirred evenly to form a coating, a layer of coating is applied on the outer wall of the hydrogel layer, and another layer is applied after the coating is dried, and this is repeated for 5 layers to form a water-retaining film.
[0066] Example 3
[0067] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0068] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 579.39 parts of phosphoric acid and 200.11 parts of water.
[0069] The present application also discloses a method for preparing a phosphogypsum-modified acid-activated geopolymer. The difference between the method for preparing a phosphogypsum-modified acid-activated geopolymer in this embodiment and that in embodiment 1 is that:
[0070] In step S4, the steps of curing and demolding the slurry are as follows: placing the mold in a steam curing chamber for steam curing to solidify the slurry in the mold, then demolding the module in the mold, and coating the outside of the module with a hydrogel layer, then coating the outer wall of the hydrogel layer with a water-retaining film, and then curing the module at room temperature for 8 days before removing the hydrogel layer and the water-retaining film.
[0071] The steps of steam curing are as follows: wrap a plastic film on the surface of the mold, place the mold in a steam curing room at a temperature of 25°C and let it stand for 6 hours, then introduce steam into the steam curing room to raise the temperature in the steam curing room to 70°C, and control the temperature rise rate to 8°C / h, then maintain constant temperature for 14 hours, then reduce the temperature in the steam curing room to 35°C, and control the cooling rate to 7°C / h, then demold and complete steam curing.
[0072] The hydrogel layer includes the following raw material components in parts by weight: 340 parts of starch, 220 parts of gelatin, 45 parts of sodium silicate, 70 parts of hyaluronic acid, 23 parts of sodium polyacrylate, 20 parts of acrylamide, 10 parts of ammonium persulfate, 8 parts of calcium carbonate, 6 parts of polyethylene glycol, 8 parts of sodium lactate, 14 parts of stearyl alcohol, 4 parts of calcium chloride and 230 parts of water.
[0073] The steps of wrapping the hydrogel layer on the outside of the module are as follows: placing the module after steam curing and demolding in a box, so that the module is in contact with the inner bottom wall of the box, and the side wall of the module is spaced from the inner wall of the box, the raw materials of the hydrogel layer are mixed and stirred evenly to form a slurry, and then a part of the slurry is injected into the box and submerged into the module, and the box is allowed to stand for 1.8 hours in an environment with a temperature of 46°C, so that the slurry condenses into a solid hydrogel layer and is coated on the outside of the side walls and top wall of the module, and then the module and the hydrogel layer are taken out of the box and turned 180 degrees and placed back in the box, and the remaining slurry is injected into the box and submerged into the module, and the box is allowed to stand for 1.6 hours in an environment with a temperature of 46°C, so that the slurry condenses into a solid hydrogel layer and completely coats the outside of the module, and then the module and the hydrogel layer coating the outside of the module are taken out of the box.
[0074] The water-retaining film comprises the following raw material components in parts by weight: 8 parts of dimer acid polyester polyol, 6 parts of hexafluorobutyl methacrylate, 12 parts of ethylene glycol, 3 parts of stannous isooctanoate, 35 parts of paraffin wax, 7 parts of zinc stearate, 13 parts of oxidized polyethylene wax, 9 parts of ethylene bisstearamide and 55 parts of water.
[0075] The steps of coating the water-retaining film on the outer wall of the hydrogel layer are as follows: the raw materials of the water-retaining film are mixed and stirred evenly to form a coating, a layer of coating is applied on the outer wall of the hydrogel layer, and another layer is applied after the coating is dried, and this is repeated for 8 layers to form a water-retaining film.
[0076] Example 4
[0077] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0078] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 144 parts of fly ash, 576 parts of metakaolin, 515.01 parts of phosphoric acid and 200.11 parts of water.
[0079] The present application also discloses a method for preparing a phosphogypsum-modified acid-activated geopolymer. The difference between the method for preparing a phosphogypsum-modified acid-activated geopolymer in this embodiment and that in embodiment 1 is that:
[0080] In step S4, the steps of curing and demolding the slurry are as follows: placing the mold in a steam curing chamber for steam curing to solidify the slurry in the mold, then demolding the module in the mold, and coating the outside of the module with a hydrogel layer, then coating the outer wall of the hydrogel layer with a water-retaining film, and then curing the module at room temperature for 10 days before removing the hydrogel layer and the water-retaining film.
[0081] The steps of steam curing are as follows: wrap a plastic film on the surface of the mold, place the mold in a steam curing room at a temperature of 30°C and let it stand for 8 hours, then introduce steam into the steam curing room to raise the temperature in the steam curing room to 80°C, and control the temperature rise rate to 10°C / h, then maintain constant temperature for 16 hours, then reduce the temperature in the steam curing room to 40°C, and control the cooling rate to 9°C / h, then demold and complete steam curing.
[0082] The hydrogel layer includes the following raw material components in parts by weight: 360 parts of starch, 240 parts of gelatin, 50 parts of sodium silicate, 75 parts of hyaluronic acid, 25 parts of sodium polyacrylate, 23 parts of acrylamide, 14 parts of ammonium persulfate, 10 parts of calcium carbonate, 8 parts of polyethylene glycol, 10 parts of sodium lactate, 15 parts of stearyl alcohol, 6 parts of calcium chloride and 250 parts of water.
[0083] The steps of wrapping the hydrogel layer on the outside of the module are as follows: placing the module after steam curing and demolding in a box, so that the module is in contact with the inner bottom wall of the box, and the side wall of the module is spaced from the inner wall of the box, the raw materials of the hydrogel layer are mixed and stirred evenly to form a slurry, and then a part of the slurry is injected into the box and submerged into the module, and the box is allowed to stand for 2 hours in an environment at a temperature of 50°C, so that the slurry condenses into a solid hydrogel layer and is coated on the outside of the side walls and top wall of the module, and then the module and the hydrogel layer are taken out of the box and turned 180 degrees and placed back in the box, and the remaining slurry is injected into the box and submerged into the module, and the box is allowed to stand for 1.8 hours in an environment at a temperature of 50°C, so that the slurry condenses into a solid hydrogel layer and completely coats the outside of the module, and then the module and the hydrogel layer coating the outside of the module are taken out of the box.
[0084] The water-retaining film comprises the following raw material components in parts by weight: 10 parts of dimer acid polyester polyol, 8 parts of hexafluorobutyl methacrylate, 15 parts of ethylene glycol, 4 parts of stannous isooctanoate, 40 parts of paraffin wax, 8 parts of zinc stearate, 15 parts of oxidized polyethylene wax, 10 parts of ethylene bisstearamide and 60 parts of water.
[0085] The steps of coating the water-retaining film on the outer wall of the hydrogel layer are as follows: the raw materials of the water-retaining film are mixed and stirred evenly to form a coating, a layer of coating is applied on the outer wall of the hydrogel layer, and another layer is applied after the coating is dried, and this is repeated for 10 layers to form a water-retaining film.
[0086] Example 5
[0087] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0088] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 0 parts of fly ash, 720 parts of metakaolin, 211.76 parts of phosphoric acid and 279.9 parts of water.
[0089] Example 6
[0090] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0091] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 360 parts of phosphogypsum, 0 parts of fly ash, 540 parts of metakaolin, 158.82 parts of phosphoric acid and 330.3 parts of water.
[0092] Example 7
[0093] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0094] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 388.8 parts of phosphoric acid and 261 parts of water.
[0095] The present application also discloses a method for preparing a phosphogypsum-modified acid-activated geopolymer. The difference between the method for preparing a phosphogypsum-modified acid-activated geopolymer in this embodiment and that in embodiment 1 is that:
[0096] In step S4, the steps of curing and demolding the slurry are as follows: wrap the outside of the mold with a plastic film, then put it into a plastic fresh-keeping bag, spray a small amount of water in the plastic fresh-keeping bag with a spray bottle, and seal the plastic fresh-keeping bag to prevent water evaporation, and then place the mold in a room temperature environment for curing for 7 days before demolding.
[0097] Example 8
[0098] The embodiments of the present application disclose a phosphogypsum-modified acid-activated geopolymer.
[0099] A phosphogypsum-modified acid-activated geopolymer comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 388.8 parts of phosphoric acid and 261 parts of water.
[0100] The present application also discloses a method for preparing a phosphogypsum-modified acid-activated geopolymer. The difference between the method for preparing a phosphogypsum-modified acid-activated geopolymer in this embodiment and that in embodiment 1 is that:
[0101] In step S4, the steps of curing and demolding the slurry are as follows: wrap the outside of the mold with a plastic film, then put it into a plastic fresh-keeping bag, spray a small amount of water in the plastic fresh-keeping bag with a spray bottle, and seal the plastic fresh-keeping bag to prevent water evaporation, and then place the mold in an oven at a temperature of 55°C for curing for 1 day before demolding, and then continue to cure in the oven at a temperature of 55°C for 6 days.
[0102] Comparative Example 1
[0103] This comparative example provides a phosphogypsum alkali-activated geopolymer.
[0104] A phosphogypsum alkali-activated geopolymer comprises the following raw material components in parts by weight: 60 parts of phosphogypsum, 380 parts of slag, 420 parts of fly ash, 290 parts of sodium hydroxide solution and 250 parts of water.
[0105] This comparative example also provides a method for preparing phosphogypsum alkali-activated geopolymer.
[0106] A method for preparing phosphogypsum alkali-activated geopolymer comprises the following preparation steps:
[0107] S1. Add phosphogypsum, slag, fly ash and water into a mixing pot and stir well to mix;
[0108] S2. Add sodium hydroxide solution to the material mixed in step S1, and stir and mix thoroughly;
[0109] S3. The material mixed evenly in step S2 is loaded into a mold, and after curing, the mold is demoulded to form phosphogypsum alkali-activated geopolymer.
[0110] Comparative Example 2
[0111] The difference between this comparative example and comparative example 1 is that a phosphogypsum alkali-activated geopolymer comprises the following raw material components in parts by weight: 70 parts of phosphogypsum, 390 parts of slag, 430 parts of fly ash, 300 parts of sodium hydroxide solution and 260 parts of water.
[0112] Comparative Example 3
[0113] The difference between this comparative example and comparative example 1 is that a phosphogypsum alkali-activated geopolymer comprises the following raw material components in parts by weight: 80 parts of phosphogypsum, 400 parts of slag, 440 parts of fly ash, 310 parts of sodium hydroxide solution and 270 parts of water.
[0114] The performance of the acid-activated geopolymers modified with phosphogypsum prepared in Examples 1-8 and the alkali-activated geopolymers prepared in Comparative Examples 1-3 were tested. The raw material component formulas of the examples and comparative examples are shown in Appendix 3 and 4, and the test results are shown in Appendix 5.
[0115] Appendix 3: Raw material composition ratio of phosphogypsum modified acid activated geopolymer
[0116]
[0117] Appendix 4: Raw material composition ratio of phosphogypsum alkali activated geopolymer
[0118]
[0119] Appendix 5 Working properties of phosphogypsum modified acid activated geopolymer and phosphogypsum alkali activated geopolymer
[0120]
[0121] From the data analysis of Appendix 5, it can be seen that the phosphogypsum modified acid-activated geopolymer prepared by the raw material components and preparation method of the embodiment of the present application has a lower dielectric constant and a higher density than the phosphogypsum alkali-activated geopolymer of the comparative example, so that it has good insulation and a denser structure, which can show better mechanical properties and durability, so that the acid-activated geopolymer can maintain stable performance even in extreme environments.
[0122] The embodiments of this specific implementation are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. The same components are represented by the same figure marks. Therefore, any equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A phosphogypsum-modified acid-activated geopolymer, characterized in that: The invention comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 36-144 parts of fly ash, 576-684 parts of metakaolin, 388.8-611.58 parts of acid activator and 200.11-261 parts of water.
2. The phosphogypsum modified acid-activated geopolymer according to claim 1, characterized in that: The acid activator is phosphoric acid.
3. The phosphogypsum modified acid-activated geopolymer according to claim 2, characterized in that: The invention comprises the following raw material components in parts by weight: 180 parts of phosphogypsum, 72 parts of fly ash, 648 parts of metakaolin, 388.8 parts of phosphoric acid and 261 parts of water.
4. A method for preparing phosphogypsum modified acid-activated geopolymer, characterized in that: The method is prepared according to the raw material components of the phosphogypsum modified acid-activated geopolymer as described in claim 1.
5. The method for preparing the phosphogypsum modified acid-activated geopolymer according to claim 4, characterized in that: The following steps are involved: S1. Mix phosphoric acid and water to make a phosphoric acid solution, and let it stand to room temperature; S2. The phosphogypsum, fly ash and kaolin are stirred and mixed evenly, and then the prepared phosphoric acid solution is poured and stirred and mixed evenly to form a slurry; S3. Pour the slurry into the mold, vibrate to eliminate bubbles in the slurry, and smooth the surface; S4. Curing and demolding the slurry to prepare phosphogypsum modified acid-activated geopolymer.
6. The method for preparing the phosphogypsum modified acid-activated geopolymer according to claim 5, characterized in that: In step S4, the steps of curing and demolding the slurry are as follows: wrapping the outside of the mold with a plastic film, then putting it into a plastic bag, spraying water in the plastic bag, and sealing the plastic bag, curing it in an environment with a temperature of 55°C for 1 day, and then continuing to cure it at room temperature for 7 days after demolding.
7. The method for preparing phosphogypsum modified acid-activated geopolymer according to claim 5, characterized in that: In step S4, the steps of curing and demolding the slurry are as follows: placing the mold in a steam curing chamber for steam curing to solidify the slurry in the mold, then demolding the module in the mold, and coating the outside of the module with a hydrogel layer, then coating the outer wall of the hydrogel layer with a water-retaining film, and then curing the module at room temperature for 7-10 days before removing the hydrogel layer and the water-retaining film.
8. The method for preparing the phosphogypsum modified acid-activated geopolymer according to claim 7, characterized in that: The hydrogel layer comprises the following raw material components in parts by weight: 320-360 parts of starch, 200-240 parts of gelatin, 40-50 parts of sodium silicate, 60-75 parts of hyaluronic acid, 20-25 parts of sodium polyacrylate, 16-23 parts of acrylamide, 8-14 parts of ammonium persulfate, 7-10 parts of calcium carbonate, 5-8 parts of polyethylene glycol, 5-10 parts of sodium lactate, 12-15 parts of stearyl alcohol, 2-6 parts of calcium chloride and 210-250 parts of water; The step of wrapping the hydrogel layer on the outside of the module is as follows: placing the module after steam curing and demoulding in a box, so that the module is in contact with the inner bottom wall of the box, and the side wall of the module is spaced from the inner side wall of the box, mixing and stirring the raw materials of the hydrogel layer to evenly form a slurry, then injecting a portion of the slurry into the box and submerging the module, and leaving the box at a temperature of 42-50° C. for 1.5-2 hours to allow the slurry to condense into a solid hydrogel layer and coat the outside of the side wall and top wall of the module, then taking the module and the hydrogel layer out of the box, turning them 180 degrees, and then placing them back in the box, injecting the remaining slurry into the box and submerging the module, and then leaving the box at a temperature of 42-50° C. for 1.2-1.8 hours to allow the slurry to condense into a solid hydrogel layer and completely coat the outside of the module, and then taking the module and the hydrogel layer coating the outside of the module out of the box.
9. The method for preparing phosphogypsum modified acid-activated geopolymer according to claim 7, characterized in that: The steps of steam curing are as follows: coating the surface of the mold with a plastic film, placing the mold in a steam curing room at a temperature of 20-30° C. and leaving it to stand for 4-8 hours, then introducing steam into the steam curing room to raise the temperature in the steam curing room to 60-80° C., and controlling the temperature rise rate to 5-10° C. / h, then curing at a constant temperature for 12-16 hours, then reducing the temperature in the steam curing room to 30-40° C., and controlling the cooling rate to 6-9° C. / h, and then demolding to complete the steam curing.
10. The method for preparing phosphogypsum modified acid-activated geopolymer according to claim 7, characterized in that: The water-retaining film comprises the following raw material components in parts by weight: 5-10 parts of dimer acid polyester polyol, 5-8 parts of hexafluorobutyl methacrylate, 10-15 parts of ethylene glycol, 2-4 parts of stannous isooctanoate, 30-40 parts of paraffin wax, 6-8 parts of zinc stearate, 12-15 parts of oxidized polyethylene wax, 8-10 parts of ethylene bis stearamide and 50-60 parts of water; The steps of coating the water-retaining film on the outer wall of the hydrogel layer are as follows: the raw materials of the water-retaining film are mixed and stirred evenly to form a coating, a layer of coating is applied on the outer wall of the hydrogel layer, and another layer is applied after the coating is dried, and this is repeated for 5-10 layers to form a water-retaining film.
Citation Information
Patent Citations
Phosphogypsum-based geopolymer and preparation method thereof
CN115159874A
Cited By
Anti-cracking phosphoric acid-based geopolymer, anti-cracking recycled aggregate, and preparation method and application of anti-cracking phosphoric acid-based geopolymer and anti-cracking recycled aggregate
CN121362005A